DOES ENVIRONMENTAL, SOCIAL, AND GOVERNANCE AFFECT FIRM VALUE? THE MEDIATING ROLE OF FINANCING CONSTRAINTS IN SOUTHEAST ASIA - Iffa Vadilla As'ad; Arief Wibisono Lubis (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
This study aims to evaluate the effect of Environmental, Social, and Governance (ESG) performance on firm value by considering financing constraints as a mediating variable. The study is conducted on non-financial companies listed in the Southeast Asian region, including Indonesia, Malaysia, Singapore, the Philippines, and Thailand during the period 2014 to 2023. Firm value is measured through Tobin's Q ratio, ESG is measured by ESG score taken from Refinitiv Eikon, while financing constraints are assessed using KZ Index. The analysis method used is panel data regression and mediation test using Sobel method. The results show that ESG performance has a positive influence on firm value in Southeast Asia. In addition, financing constraints proved to be a mediator, where improving ESG performance can reduce financing constraints, which in turn contributes to increasing firm value. Regression tests of each country and the three pillars in ESG were also conducted. From the calculation, there is significant variation, which is not captured in the combined panel model. This suggests that there is structural and contextual heterogeneity affecting the relationship of ESG to firm value in each country or each aspect of ESG.